Systematic review: Early versus late dangling after free flap reconstruction of the lower limb. Issue 8 (August 2017) - McGhee, J.T.; Cooper, L.; Orkar, K.; Harry, L.; Cubison, T.
Summary: Introduction and aims: Dangling regimes after free flap surgery to the lower limb vary between centres and clinicians. There is currently no accepted gold standard. This review examines the evidence for early versus late post-operative dangling after free flap reconstruction of the lower limb. The secondary aim is to evaluate the regimes used. Material and methods: Medline, Embase and the Cochrane library were searched for all studies on dangling or rehabilitation after free flap reconstruction in the lower limb (December 2015). All studies outlining a clear dangling regime were included. Data were extracted by two authors independently and analysed using the software package Review Manager (RevMan 5). All authors were contacted for further information. Results: 197 patients were included from 8 studies: 1 randomized, 6 cohort and 1 case-series. Although some studies did not state the aetiology, of those that did; 42% were trauma, 31% oncology, 20% complex wounds and 7% infection. The majority of flaps were latissimus dorsi, 18% parascapular, 15% anterolateral thigh and the remainder was mixed. Forty-eight percent of patients dangled on post-operative day (POD) 7, 29% on day 6, 4% on day 5 and 18% on day 3, with varying regimes. A meta-analysis of comparable studies showed circulatory benefit after 4 days of dangling using tissue oxygen saturation as a measure. Four flap failures (2.0%) were reported. Conclusions: There is physiological benefit in post-operative dangling. A 3-day flap training regime is sufficient for physiological training. However, the optimal flap training regime remains unclear. It may be appropriate to start dangling as early as POD 3. More research is needed to determine the optimal time to start dangling and the regime.